Chemical model of the FeCl3-HCl-H2O solutions at 25 degrees C - Lee, MS; Ahn, JG; Oh, YJ (JAPAN INST METALS, 2003)
A chemical model was developed to calculate the equilibrium concentrations of chemical species in the FeCl3-HCl-H2O system at 25degreesC by using chemical equilibria. mass and charge balance equations. The activity coefficients of solutes and the activity of water were calculated with the Bromley equation. The interaction parameters for the individual chemical complexes, which were necessary to calculate the activity coefficients. were obtained from the reported interaction parameters between ions. By applying this model, the distribution of iron species with the electrolyte concentrations was obtained. In the experimental ranges of the ionic strength of solution up to 7.28 m, the experimental pH values were in good agreement with the predicted pH values.
Keywords: FERRIC-CHLORIDE; STRONG ELECTROLYTES; AQUEOUS-SOLUTIONS; EXTRACTION; CHALCOPYRITE; EQUILIBRIA; IRON(III); WATER